Iron-sulfur complex assembly: Potential players of magnetic induction in plants. (December 2022) - Parmagnani, Ambra S.; D'Alessandro, Stefano; Maffei, Massimo E.
Abstract: Iron-sulfur (Fe-S) clusters are involved in fundamental biological reactions and represent a highly regulated process involving a complex sequence of mitochondrial, cytosolic and nuclear-catalyzed protein-protein interactions. Iron-sulfur complex assembly (ISCA) scaffold proteins are involved in Fe-S cluster biosynthesis, nitrogen and sulfur metabolism. ISCA proteins are involved in abiotic stress responses and in the pigeon they act as a magnetic sensor by forming a magnetosensor (MagS) complex with cryptochrome (Cry). MagR gene exists in the genomes of humans, plants, and microorganisms and the interaction between Cry and MagR is highly conserved. Owing to the extensive presence of ISCA proteins in plants and the occurrence of homology between animal and human MagR with at least four Arabidopsis ISCAs and several ISCAs from different plant species, we believe that a mechanism similar to pigeon magnetoperception might be present in plants. We suggest that plant ISCA proteins, homologous of the animal MagR, are good candidates and could contribute to a better understanding of plant magnetic induction. We thus urge more studies in this regard to fully uncover the plant molecular mechanisms underlying MagR/Cry mediated magnetic induction and the possible coupling between light and magnetic induction. Graphical Abstract: ga1 Highlights: Iron-sulfur complex assembly (ISCA) scaffold proteins are involved in abiotic stress. In the pigeon ISCA act as a magnetic sensor by forming a magnetosensor (MagS) complex with cryptochrome. There is homology between animal and human MagR with at least four Arabidopsis ISCAs. A mechanism similar to pigeon magnetoperception might be present in plants. Plant MagR/Cry mediated magnetic induction might explain plant responses to varying magnetic fields.